Comments on the paper "Synthesis, structural and optical properties, ferromagnetic behaviour, cytotoxicity and NLO activity of lithium sulphate doped l-threonine". (November 2021) - Srinivasan, Bikshandarkoil R.; Deshpande, Megha S.; Morajkar, Sudesh M.
Graphical abstract: Slow evaporation of an aqueous solution containing equimolar quantities of l- threonine and lithium sulphate monohydrate results in the fractional crystallization of l- threonine. Highlights: The title paper is critiqued. Crystal growth of lithium sulphate doped l -threonine is reinvestigated. Lithium sulphate doped l -threonine is, in fact, l -threonine. l -threonine is a diamagnetic solid. Abstract: The authors of the title paper (Optics and Laser Technology 83 (2016) 49–54) claim to have grown a 'lithium sulphate doped l -threonine' crystal by slow evaporation of an aqueous solution containing equimolar amounts of l- threonine and lithium sulphate. A reinvestigation of the crystal growth reaction reveals that fractional crystallization of l -threonine occurs. In this letter to the Editor, we prove that the so-called lithium sulphate doped l -threonine is a dubious crystal and not a ferromagnetic material